THE BATTLE OF KOŠARE AS A LIEU DE MÉMOIRE OF THE MILITARY PROFESSION - Vukadinovic, Marija (Political Review, 2025)
This paper examines the importance of the culture of remembrance for the military profession in Serbia, with a particular focus on the Battle of Košare as a lieu de mémoire. It explores the relationship between collective memory, historical narratives, and the identity foundations of the military profession within contemporary Serbian society, especially in light of ongoing political and security transformations. Drawing on the theoretical framework of Pierre Nora and existing interpretations of the interplay between history and memory, the paper analyzes memory as an active resource for preserving national identity. The research argues that collective memory is not merely a tool for safeguarding historical heritage but also a vital element in shaping moral and professional continuity. The methodological approach is grounded in qualitative analysis of relevant sources, including academic literature and historical documents that serve as testimonies of the past. The findings suggest that the process of European integration may indirectly affect the visibility of certain historical narratives, with the role of individual heroes, such as those who fought in the Battle of Košare, remaining underrepresented in official narratives and public discourse. The paper concludes that institutionalizing the memory of the Battle of Košare is essential not only for reinforcing national identity but also for upholding the professional and ethical values that underpin military service. By embedding this memory in official discourse and incorporating it into educational and institutional initiatives, the military reinforces its continuity and affirms its role as a custodian of values such as duty, sacrifice, and loyalty-qualities that are crucial for sustaining discipline and professional integrity. Institutionalizing this memory also helps ensure that the significance of the Battle of Košare is properly recognized and passed on to future generations. This, in turn, shapes both public understanding and the international perception of the Serbian military.
Keywords: culture of remembrance; military profession; military identity; Serbian Army; duty